STATE RESPONSIBILITY IN ENFORCEMENT OF CITIZENS' CONSTITUTIONAL RIGHTS IN LAND EXECUTION CASES IN TIMOR LESTE - Remigio Pereira da Cruz; Carolina da Cruz (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The purpose of this study is to explain and understand the State's Responsibility in Enforcing Citizens' Constitutional Rights in Land Execution Cases in Timor Leste. To explain and understand the Indonesian Government in this case to realize protection and justice for its citizens whose land rights are threatened or lost after the release of Timor Leste. This research uses a normative juridical legal research method. The type of approach used in this research is a case study approach. The sources of normative legal research are primary legal materials, secondary legal materials, and non-legal materials. This study uses a qualitative analysis method. Based on the conclusion that the responsibility of the Timor-Leste state in enforcing the constitutional rights of citizens in land execution cases is represented by the development of land laws to harmonize various legal regimes, namely by developing laws that combine and clarify land rights and the process of claims that are violated and recognize property rights and clarify the legal status of immovable property. The state is also responsible for protecting and upholding the rights of citizens as a whole as stated in the Constitution. The Indonesian government has sought to provide protection and justice for citizens who lost their land rights after the secession of Timor-Leste through various policies, including the establishment of the Truth and Friendship Commission to address human rights violations, and support for resolving land issues through various legal and non-legal mechanisms. However, these efforts often face challenges of legal and bureaucratic complexity, which require special and comprehensive handling from the government.